2020
DOI: 10.3389/fcell.2020.00726
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Alpha-Synuclein Fibrillization by Protein Disulfide Isomerase

Abstract: Aggregates of α-synuclein contribute to the etiology of Parkinson's Disease. Protein disulfide isomerase (PDI), a chaperone and oxidoreductase, blocks the aggregation of α-synuclein. An S-nitrosylated form of PDI that cannot function as a chaperone is associated with elevated levels of aggregated α-synuclein and is found in brains afflicted with Parkinson's Disease. The protective role of PDI in Parkinson's Disease and other neurodegenerative disorders is linked to its chaperone function, yet the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…This result points to an autoinhibitory role for the C-terminus on fibrillation, consistent with the previous studies 20,23,60 . As expected, the presence of PDI inhibits FL-α-syn aggregation 52,61,62 , but inhibits CT-α-syn aggregation to a somewhat smaller extent, as reflected by an over 3-fold increase in lag time for FL-α-syn whereas less than 2-fold for CT-α-syn. Besides, half-time of aggregation (t 1/2 ) clearly shows that PDI exerted a less inhibitory effect on CT-αsyn aggregation (Fig.…”
Section: Resultssupporting
confidence: 76%
“…This result points to an autoinhibitory role for the C-terminus on fibrillation, consistent with the previous studies 20,23,60 . As expected, the presence of PDI inhibits FL-α-syn aggregation 52,61,62 , but inhibits CT-α-syn aggregation to a somewhat smaller extent, as reflected by an over 3-fold increase in lag time for FL-α-syn whereas less than 2-fold for CT-α-syn. Besides, half-time of aggregation (t 1/2 ) clearly shows that PDI exerted a less inhibitory effect on CT-αsyn aggregation (Fig.…”
Section: Resultssupporting
confidence: 76%
“…its neuroprotective action resides in ERp57 impairment of peptide aggregation, rather than in disaggregation of existing fibrils. The inhibition of the aggregation was induced by low amounts of ERp57 protein, present in the reaction mixture in a very low molar ratio compared to the peptide (1:250), in line with the experiments conducted by Serrano and coworkers, who demonstrated that ERp57 is able to reduce the aggregation of α-synuclein in a very efficient manner, in a 1:50 molar ratio(Serrano et al, 2020). The efficiency ofERp57, even at a low molar ratio compared to Aβ 25−35 , indicates that ERp57 may bind oligomeric Aβ 25−35 .…”
supporting
confidence: 88%
“…Many literature reports indicate that ERp57 is a multifunctional protein with a high propensity to interact with peptides and proteins prone to misfolding, such as PrP (Hetz et al, 2005; Thapa et al, 2018; Torres et al, 2015) and α‐synuclein (Serrano et al, 2020). Moreover, other members of the PDI family are able to bind tau protein (Xu et al, 2013) and proteins without disulfide bonds (Cai et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also confirmed inhibited fibrillization by PDI. Later, it was also shown that PDI can break down nascent α-Syn fibrils, yet not mature fibrils [ 114 ]. The redox balance in the ER impacts the S-nitrosylation state of PDI [ 115 ].…”
Section: Redox Imbalance and Protein Misfolding In Neurodegenerationmentioning
confidence: 99%